CLASS CONFLICT AND CHANCE IN THOMAS HARDY’S TESS OF THE D’URBERVILLES: A MARXIST INTERPRETATION - Shihab, Md. Nuruddin Pier (Sanata Dharma University, Yogyakarta, 2024)
This study sets a Marxist lens to explore class conflict and the interplay of fate in Thomas Hardy’s Tess of the d’Urbervilles. The paper examines Tess’s representation as a victim of the Victorian class system and sexual oppression, investigating whether her tragic downfall results from chance or her subordinate social position. The evolving social statuses of central characters like Tess, Angel, and Alec add various dimensions to the narrative tension of the book. By utilizing the qualitative-descriptive method and Marxist concepts of class conflict and capitalism, the analysis accentuates how economic stability, or the lack thereof, intricately influences personal lives and relationships in Victorian society. Tess exemplifies the oppressed working class, while oppressors like Alec and Angel exercise their predatory dominance over her. Moreover, the research article aims to highlight the pivotal role of fate and chance in shaping Tess’s destiny, with coincidences and unexpected events intensifying her misfortunes. Ultimately, the research paper posits that economic fragility not only subjugates the working class but can also precipitate the downfall of the oppressors themselves.